Heteroatom-doped graphene as sensing materials: a mini review. Issue 48 (4th August 2020) - Kaushal, Sandeep; Kaur, Manpreet; Kaur, Navdeep; Kumari, Vanita; Singh, Prit Pal
Abstract : Graphene is one of the astounding recent advancements in current science and one of the most encouraging materials for application in cutting-edge electronic gadgets. Abstract : Graphene is one of the astounding recent advancements in current science and one of the most encouraging materials for application in cutting-edge electronic gadgets. Graphene and its derivatives like graphene oxide and reduced graphene oxide have emerged as significant nanomaterials in the area of sensors. Furthermore, doping of graphene and its derivatives with heteroatoms (B, N, P, S, I, Br, Cl and F) alters their electronic and chemical properties which are best suited for the construction of economical sensors of practical utility. This review recapitulates the developments in graphene materials as emerging electrochemical, ultrasensitive explosive, gas, glucose and biological sensors for various molecules with greater sensitivity, selectivity and a low limit of detection. Apart from the most important turn of events, the properties and incipient utilization of the ever evolving family of heteroatom-doped graphene are also discussed. This review article encompasses a wide range of heteroatom-doped graphene materials as sensors for the detection of NH3, NO2, H2 O2, heavy metal ions, dopamine, bleomycinsulphate, acetaminophen, caffeic acid, chloramphenicol and trinitrotoluene. In addition, heteroatom-doped graphene materials were also explored for sensitivity and selectivity with respect to interfering analytes present in the system. Finally, the review article concludes with future perspectives for the advancement of heteroatom-doped graphene materials.